Country Partnership Framework for the Republic of North Macedonia for the Period of January 2019-June 2023 - World Bank (World Bank, Washington, DC, 2019)
This Country Partnership Framework (CPF) sets out the World Bank Group’s approach to supporting the reform agenda in North Macedonia over January 2019–June 2023. The CPF builds on the results and lessons of the previous World Bank Group Country Partnership Strategy (CPS) that originally covered the period from July 2014 to June 2018 and was subsequently extended by six months to December 2018. The new CPF seeks to address the priorities identified by the recently completed Systematic Country Diagnostic (SCD) for North Macedonia. The strategic objective of the CPF is to support North Macedonia’s ability to achieve faster, inclusive, and sustainable growth and provide its citizens with greater opportunities for a better life. The CPF aims to support the Government’s program and medium-term strategy, which present a vision of accelerated economic growth with better employment opportunities, social cohesion and inclusion, and a plan to tackle the persistent bottlenecks. The Government strategy is consistent with the SCD’s vision of a better-connected, vibrant domestic economy engaged in the region and beyond as it secures its footing in areas of strong comparative advantage.